Influence of the Shariah supervisory board on tax avoidance at an Indonesian Islamic bank - Naufal, Ahmad; Prasojo, Prasojo; Utami, Ristianawati Dwi (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study examines the influence of the Shariah supervisory board (SSB) and Islamic banks’ characteristics on tax avoidance practices in Indonesia.Methodology – This research uses secondary data using the panel data analysis method fixed effects model; the research sample is an Islamic bank in Indonesia from 2017 to 2021.Findings – The results indicate that SSB size, SSB reputation, and bank size have a positive effect on tax avoidance. The variables across SSB members, SSB education level, bank age, and bank profitability have a negative effect. Meanwhile, the SSB expertise variable, SSB remuneration, and turnover do not affect tax avoidance.Implications – Islamic banks play an essential role in social welfare to align with tax contributions in developing countries. Therefore, tax regulators and Islamic banks must collaborate to review the treatment of expenses according to tax regulations.Originality – This study fills a research gap by investigating the relationship between SSB characteristics and tax avoidance in Indonesian Islamic banks, which has yet to be discussed in previous papers.